Emergency medicine physician supervision and mortality among patients receiving care from non-physician clinicians in a task-sharing model of emergency care in rural Uganda: a retrospective analysis of a single-centre training programme - Rebecca Leff; Brian Rice; Bradley Dreifuss; Heather Hammerstedt; Mark Bisanzo; Stacey Chamberlain; Ashley Pickering; Colleen Laurence; Prisca Mary Kizito; Steven Jonathan Kisingiri; Charles Ndyamwijuka; Serena Nakato; et al. (BMJ Open)
Objectives To assess the association between emergency medicine physician supervision and 3-day mortality for patients receiving care from non-physician clinicians in a task-sharing model of emergency care in rural Uganda.Design Retrospective cohort analysis with multivariable logistic regression.Setting Single rural Ugandan emergency unit.Participants All patients presenting for care from 2009 to 2019.Interventions Three cohorts of patients receiving care from non-physician clinicians had three different levels of physician supervision: ‘Direct Supervision’ (2009–2010) emergency medicine physicians directly supervised all care; ‘Indirect Supervision’ (2010–2015) emergency medicine physicians were consulted as needed; ‘Independent Care’ (2015–2019) no emergency medicine physician supervision.Primary outcome measure Three-day mortality.Results 38 033 ED visits met inclusion criteria. Overall mortality decreased significantly across supervision cohorts (‘Direct’ 3.8%, ‘Indirect’ 3.3%, ‘Independent’ 2.6%, p<0.001), but so too did the rates of patients who presented with ≥3 abnormal vitals (‘Direct’ 32%, ‘Indirect’ 19%, ‘Independent’ 13%, p<0.001). After controlling for vital sign abnormalities, ‘Direct’ and ‘Indirect’ supervision were both significantly associated with reduced OR for mortality (‘Direct’: 0.57 (0.37 to 0.90), ‘Indirect’: 0.71 (0.55 to 0.92)) when compared with ‘Independent Care’. Sensitivity analysis showed that this mortality benefit was significant for the minority of patients (17.2%) with ≥3 abnormal vitals (‘Direct’: 0.44 (0.22 to 0.85), ‘Indirect’: 0.60 (0.41 to 0.88)), but not for the majority (82.8%) with two or fewer abnormal vitals (‘Direct’: 0.81 (0.44 to 1.49), ‘Indirect’: 0.82 (0.58 to 1.16)).Conclusions Emergency medicine physician supervision of emergency care non-physician clinicians is independently associated with reduced overall mortality. This benefit appears restricted to the highest risk patients based on abnormal vitals. With over 80% of patients having equivalent mortality outcomes with independent non-physician clinician emergency care, a synergistic model providing variable levels of emergency medicine physician supervision or care based on patient acuity could safely address staffing shortages.